Sistur Hijab / Siti Zulaikha Saidun ... [et al.] - Saidun, Siti Zulaikha; Mohammad Fadli, Nur Fasha Syahira; Ngadnan, Nur’ain; Abdul Hadi, Afifah Nadiah; Muhd Adlan, Nurul Izzati (2025)
Sistur Hijab is an exclusive and ideal hijab brand that aims to provide the premium hijab materials with stylish design but adhere with Shariah principle. Through the company hijab innovation such as ironless cotton hijab materials, brooch-less hijab using magnet as a replacement, and offer a wide coverage hijab size has becoming their unique selling proposition. The company are dedicated to make the company as the choice for woman who are busy and want to save their time to get ready. Sistur Hijab was established in December 2024 and starts operating in January 2025. The company also planned to have their own branches in the whole Malaysia since majority of Malaysian people are muslim. Sistur Hijab carters to individuals who are looking for premium and comfortable hijab material. The company target market includes woman in Selangor and nearby the company factory located at Jalan SS 13, Bandar Sunway, Subang Jaya, Selangor with the estimation of 29 6400 to 691 300 population that contribute to the market size of RM 9 886 175 per month. To promote the brand and increase the sales, Sistur Hijab implemented several strategies includes advertising the product using billboards located at highway such as North-South Expressway (PLUS). The company also active on social media promoting through platform such as Instagram and TikTok. There will be a trained staff to become a host-live at the TikTok platform. Besides, the company also collaborate with a well-known figure as their brand ambassador to gain the brand exposure. The company also apply competitive pricing and offering purchase with purchase, which mean the second purchased will get discount price to increase the product purchases.